Hearing Loss in Acromegaly - A Review - Teixeira,Liane Sousa (2018)
Abstract Introduction Acromegaly is a chronic disease caused by growth hormone (GH) excess due to a GH-secreting pituitary adenoma in most cases. There is reasonable data to presume the possible influence of chronic GH and insulin-like growth factor I (IGF-I) hyperproduction on the anatomical structures involved in normal sound perception, and on its conductive and/or sensorineural part. Objectives To review the literature about acromegaly and hearing loss. Data Synthesis A systematic literature search was performed using the MEDLINE database, including hand-searching reference lists from original articles. The search was performed using the terms hearing loss and acromegaly, and only 5 studies were found. Conclusion The results are not consistent, but led to different conclusions. Therefore, more studies with greater numbers of patients with acromegaly are needed.